Stroke Risk Status, Anticoagulation Treatment, and Quality-of-Life in Chinese Patients with Atrial Fibrillation: China Registry of Atrial Fibrillation (CRAF) - Yihong Sun; Jun Zhu; Changsheng Ma; Shaowen Liu; Yanzong Yang; Dayi Hu (Hindawi-Wiley, 2019)
Objective. To investigate the contemporary status of stroke risk profile, antithrombotic treatment, and quality-of-life (QoL) of patients with all types of atrial fibrillation (AF) in China. Design. This is a multicenter, cross-sectional study. Setting. Tertiary (80%) and Tier 2 hospitals (20%) were identified in different economic regions (Northeast, East, West, and Middle) by using a simple random sampling. Participants. A total of 3562 (85.6%) patients with nonvalvular atrial fibrillation (NVAF) and 599 (14.4%) with rheumatic valvular atrial fibrillation (VAF) were consecutively enrolled from 111 hospitals from July 2012 to December 2012. Data Collection. Patient information was collected and QoL was assessed using Short-Form 36 Health Survey (SF-36) questionnaire. Primary and Secondary Outcome Measures. The risk of stroke was assessed using the CHADS2 and CHA2DS2-VASc. QoL was assessed using Medical Outcomes Study SF-36 questionnaire. Results. Overall, 31.7% of the patients received anticoagulant treatment and 61.2% received antiplatelet treatment. The rate of anticoagulant treatment was higher in patients with VAF than in those with NVAF. The anticoagulant use was the lowest in Northeast and the highest in Middle regions. Independent risk factors associated with underuse of anticoagulants for NVAF were age, systolic blood pressure (SBP), non-Middle regions, nontertiary hospitals, and new-onset or paroxysmal AF. For VAF patients, the independent factors were age, paroxysmal AF, treatment in Tier 2 hospitals, SBP, diastolic blood pressure, history of coronary artery disease, and nonreceipt of antiarrhythmic therapy. Patients receiving anticoagulants fared significantly better in some QoL domains than those who received no antithrombotic therapy. Conclusions. These findings suggest that antiplatelet treatment is overused and anticoagulant treatment is underused both in Chinese patients with VAF and NVAF, even though usage of anticoagulants is associated with better QoL. Risk factors with underuse of anticoagulants were not identical in patients with NVAF and VAF.